Psychological Stress and its Relationship with Achievement of Science Students of Jawahar Navodaya Vidhyalayas - Narendra Kumar,; Rajive Kumar, (JOURNAL OF INDIAN EDUCATION, 2013)
This study attempts to assess the psychological stress and its relationship with achievement among senior secondary science students of Jawahar Navodaya Vidhayalayas. A sample of students was randomly selected from different Jawahar Navodaya Vidhayalayas of Meerut province. They were administered Psychological Stress Scale for Science Students developed by researchers themselves which measures 12 dimensions of psychological stress. Results show that the examination and achievement have been emerged as the major factor causing stress, while health as the least causing factor for stress. Negative and significant correlation with achievement was observed for all dimensions of psychological stress except science teachers and society.